Multiple Pericallosal Lipomas in Two Siblings with Frontonasal Dysplasia - Alzoum, Mohammad A.; Alorainy, Ibrahim A.; Al Husain, Muneera; Al Ruhaimi, Khalid (American Journal of Neuroradiology, 2002)
Summary: We report cases of two siblings with frontonasal dysplasia (FND) associated with multiple pericallosal lipomas in almost similar locations. In each sibling two separate curvilinear pericallosal lipomas were present—one in relation to the posterior part of the corpus callosum and the other in relation to the rostrum. To our knowledge, multiple pericallosal lipomas in association with FND have not been described before. Pericallosal lipomas in cases of FND are of the tubulonodular type; they have been reported only in relation to the anterior part of the corpus callosum.